Nanoparticle-based therapeutic delivery of prohibitin to the colonic epithelial cells ameliorates acute murine colitis - Theiss, Arianne L. (2010)
INTRODUCTION: Intestinal epithelial expression of anti-oxidants and NF-κB contribute to mucosal barrier integrity and epithelial homoestasis, two key events in the pathogenesis of inflammatory bowel disease. Genetic restoration of intestinal epithelial prohibitin 1 (PHB) levels during experimental colitis reduces the severity of disease through sustained epithelial anti-oxidant expression and reduced NF-κB activation. To determine the therapeutic potential of restoring epithelial PHB during experimental colitis in mice, we assessed two methods of PHB colonic mucosal delivery: adenovirus-directed administration by enema and poly (lactic acid) nanoparticle (NPs) delivery by gavage. METHODS: As a proof-of-principle to demonstrate the therapeutic efficacy of PHB, we utilized adenovirus-directed administration by enema. Second, we used NPs based colonic delivery of biologically active PHB to demonstrate therapeutic use for human IBD. Colitis was induced by oral administration of dextran sodium sulfate in water for 6–7 days. Wild-type mice receiving normal tap water served as controls. RESULTS: Both methods of delivery resulted in increased levels of PHB in the surface epithelial cells of the colon and reduced severity of dextran sodium sulfate-induced colitis in mice as measured by body weight loss, clinical score, myeloperoxidase activity, pro-inflammatory cytokine expression, histological score and protein carbonyl content. CONCLUSIONS: This is the first study to show oral delivery of a biologically active protein by NPs encapsulated in hydrogel to the colon. Here we show that therapeutic delivery of PHB to the colon reduces the severity of dextran sodium sulfate-induced colitis in mice. PHB may represent a novel therapeutic target in inflammatory bowel disease.